A critical edition of the Sonate da chiesa for theorbo and organ of Giovanni Pittoni - Livingston, Donald D. (Kansas State University, 2010)
The purpose of this edition of the Sonate da chiesa for theorbo and organ from the Intavolatura di tiorba, opera prima (1669) of Giovanni Pittoni is to make available a clear, modern notation of the theorbo part, which appears in the score in Italian lute tablature, and to place the works within their performance context. This edition enables a keyboardist to read the solo theorbo part to help keep the ensemble together and to help create a continuo realization. Under usual circumstances a continuo player can read the part of the soloist and can use it to instruct how to realize the accompaniment. With tablature, however, the keyboardist is at a disadvantage, since most – practically all – do not read tablature. The accompanying text reveals how the works were used and how the continuo is to be realized, and suggests answers to the problems associated with continuo realization for bass instruments in a solo role. This score is not intended to make the music more accessible to the soloist, since theorbists are already skilled at reading tablature. Additionally, recreating the tablature was unnecessary, since the original source (or facsimile) is easily read. In addition, errors have been identified, and possible answers and solutions are provided.
Keywords: Theorbo; Pittoni; Transcription; Score; Music (0413)